“We wouldn’t of made friends if we didn’t come to Football United”: the impacts of a football program on young people’s peer, prosocial and cross-cultural relationships - Nathan, Sally; Kemp, Lynn; Bunde-Birouste, Anne; MacKenzie, Julie; Evers, Clifton; Shwe, Tun Aung (BioMed Central, 2013)
Background